The tragedy (or virtue?) of in-kind redistribution: How the poor pays for the rich's status concerns - Jan Schumacher (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
The model describes a two person economy, in which one individual with positive exogenous income is altruist towards an individual with no income. The rich individual cares for her own social status. She evaluates her status by comparing disposable net cash incomes. When deciding on the size and on the structure of redistribution, the rich person decides that at least part of the redistribution is done inkind, even if a private substitute for the publicly provided good is available. The amount of inkind transfers that is provided exceeds the unconstrained Marshallian demand of the poor individual for the good in question. Hence, optimal policy restricts the poor in his allocative choices. The overall resource transfer is lower when the richer cares for her status compared to a situation in which she does not.
Keywords: H42; D63; D64; D31; 330; Redistribution; inkind transfers; altruism; status